PERANCANGAN BUKU KOMIK EDUKASI EVENT ORGANIZER BAGI PELAJAR SMA - Yadi Syanurdi, Ir. Drs. Heldi, M.Si., Ph,.D. Drs. Mediagus, M. Pd. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The basic problem of this design is, high school students do not understand the event organizer, and are not optimal in carrying out activities or activities at the event. The purpose of this design is to help students better understand the event organizer, through an educational medium in the form of comics. The design method used is glass box, where the final result of a work has been drawn from a rational process. Data collection is done through interviews, observations, and documentation. Data will be processed using the 5W + 1H analysis approach (what, who, when, where, why, and how). Creative approach taken using supporting media: stickers, posters, t-shirts, e-books, x-banners, tote bags and note books. This educational comic will use visual characters in the form of high school children, using formal and non-formal language, and interspersed with non-comic pages and panels that contain explanations, photos, or infographics to assist in explaining the material.Keywords: Comik, Education, Event, Organizer, Student.